Narrative Review of Tracheostomy Procedure during COVID-19 Pandemic - Siti Asmat Md Arepen; Nor Azirah Salahuddin; Eyzawiah Hassan (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 02-2021) [June 2021]